(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper deals about the Analysis of Speed controller for three phase induction motor in 125/60 (Tons per hour) TPH Aggregate crushing Sand Plant. Three phase induction motor speed control is necessary to do the various operations of the aggregate crushing sand plant especially in the vibrating grizzly feeder and also in the vertical shaft impactor. As speed control of the three phase induction motor is required, it is also mandatory requirement of the speed controller. In this paper, crushing sand Plant operation is delineated and also shortcomings of the conventional speed controller PLC which is used in this plant is discussed.